Insecticide effects of Ruta graveolens, Copaifera langsdorffii and Chenopodium ambrosioides against pests and natural enemies in commercial tomato plantation - Flávia Silva Barbosa (Acta Scientiarum. Agronomy, 2011)
The aim of this study was to evaluate the insecticide effect of watery leaf extracts of Ruta graveolens (Rutaceae), alcoholic leaf extracts of Copaifera langsdorffii (Caesalpinaceae) and Chenopodium ambrosioides (Chenopodiaceae) in the concentration of 5% under field conditions. The experiment design was randomized blocks with six replications. The parcels treated with plant extracts showed reduction in the population of pests when compared with the control parcels. The extract elaborated with C. langsdorffii presented greater insecticidal effect under Bemisia tabaci (Hemiptera: Aleyrodidae) and sum of pests. It was verified that after 24 hours of spraying, the parcels treated with the extract of C. ambrosioides presented minor numbers of adults of Tuta absoluta (Lepidoptera: Gelechiidae), followed by the parcels treated with extract of R. graveolens. There were smaller numbers of parasitoid eggs of lepidopterans Trichogramma sp. (Hymenoptera: Trichogrammatidae) and sum of natural enemies (predators + parasitoids) in the parcels that had received spraying with extracts from the plants of C. langsdorffii and C. ambrosioides, followed by R. graveolens, compared to the control. There were a smaller number of parasitoids from the family Eulophidae (Hymenoptera) attacking caterpillars of T. absoluta in plants treated with R. graveolens, followed by C. langsdorffii and C. ambrosioides than in the control.